2002
DOI: 10.1073/pnas.022647099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of folivory on photosynthesis is greater than the sum of its holes

Abstract: The effects of herbivores on plant production and fitness may not relate directly to the quantity of biomass removed because folivory may alter photosynthetic rates at a considerable distance from the damaged tissue [ ]. An impediment to understanding the effects of leaf damage on photosynthesis has been an inability to map photosynthetic function within a single leaf. We developed an instrument for imaging chlorophyll fluorescence and used it to map the effects of caterpillar feeding on whole-leaf photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
257
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(273 citation statements)
references
References 18 publications
11
257
2
3
Order By: Relevance
“…For example, our estimates did not account for leaves that were abscised after arthropod damage, which could underestimate leaf loss by up to 50% (29). Also, recent work has shown that simply measuring holes in leaves, as in this study, may underestimate by a factor of 6 the actual damage to photosynthetic tissue caused by chewing insects (30).…”
Section: Discussionmentioning
confidence: 95%
“…For example, our estimates did not account for leaves that were abscised after arthropod damage, which could underestimate leaf loss by up to 50% (29). Also, recent work has shown that simply measuring holes in leaves, as in this study, may underestimate by a factor of 6 the actual damage to photosynthetic tissue caused by chewing insects (30).…”
Section: Discussionmentioning
confidence: 95%
“…Reduced photosynthetic capacity can exceed what would be expected from the observed amount of foliar tissue that is removed (Zangerl et al, 2002). However, actual insect damage is not a prerequisite for reduced photosynthetic activity.…”
Section: Carbohydrate Metabolismmentioning
confidence: 86%
“…Giri et al (2006) reported that the amount of proteins involved in photosynthesis decreased in N. attenuata leaves when they were wounded and treated with oral secretions of M. sexta, which probably resulted in a reduced rate of photosynthesis. Such negative impacts from herbivory on photosynthetic activity have been reported (Zangerl et al 2002). In contrast, little change in photosynthetic activity in the volatile exposed lima bean plants was detected in a previous study (Arimura et al 2000a).…”
Section: (Cv) 30 Kda (-)Tpenvelvftdqvtqpsdtdlgak(-) O49079; (-)Tpenvementioning
confidence: 57%